Double Photoionization of confined atoms in n-walled fullerenes. (August 2015) - Randazzo, J M; Frapiccini, A L; Mitnik, D; Gasaneo, G; Colavecchia, F D
Synopsis: In this work we study the effect of fullerene confinement on the triple differential cross section (TDCS) for double ionization of atoms. We compare the results corresponding to the free case with single cage C 60 and two cage C 60 @ C 240 confinement.